Influencia del modelo de seguridad vial ISO-39001 en la accidentabilidad de transportes Línea S.A., Trujillo 2017 - 2018 - Amaya Alvarado, Paolo Andre (2019)
ABSTRACT The purpose of the research was to determine the influence of the road safety management model-ISO 39001, on the reduction of accidents in Transportes Linea. The sample consisted of the transport operations of mining personnel of the company (632 people), direct observation and documentary review of the company that intervened in the investigation was used as a technique for the collection of road events that occurred over time, the methodology used for the determination of risks were the Ishikawa diagram, the operational controls were developed through the brainstorming and guidelines of the ISO 39001: 2012 standard. It was determined that the greatest presence of risk was linked to the driver, maintenance, and the road; Also, chafing was the most frequent type of incident, while stone splashes and road faults presented a lower incidence during the investigation period. The operational controls that stood out were the GPS control through geo-fences, the control of Fatigue and drowsiness; the linear model was the one that describes the behavior of road events in relation to time. Concluding the existence of a significant trend in reducing road events by applying a road safety model, based on ISO 39001.